Random Walk Modeling for Retrieving Information on Semantic Networking - Meghdad Abarghouei Nejad; Azizollah Memariani; Javad Hatami; Masoud Asadpour (Mathematics Interdisciplinary Research, 2020)
In this article, the famous random walk model is exploited as a model of stochastic processes to retrieve some specific words which are used in social media by users. By spreading activation on semantic networking, this model can predict the probability of the words' activation, including all probabilities in different steps. In fact, the trend of probability in different steps is shown and the result of two different weights, when the steps tend to infinity is compared. In addition, it is shown that the results of the random walk model are aligned with the experimental psychological tests, showing that, as a model for semantic memory, it is a suitable model for retrieving in social media.